Fractal-seaweeds type functionalization of graphene. (March 2020) - Amsharov, Konstantin; Sharapa, Dmitry I.; Vasilyev, Oleg A.; Oliver, Martin; Hauke, Frank; Goerling, Andreas; Soni, Himadriben; Hirsch, Andreas
Abstract: In this work, we present a systematic investigation on the regioselectivity and topicity of radical hydrogenation/alkylation of graphene. The complex process of sequential covalent binding of hydrogen and methyl radicals to the edges and basal plane of graphene, and addition to the direct neighborhood of pre-existing defects were quantitatively investigated using different computational techniques. Considering both thermodynamic and kinetic factors a general model for graphene functionalization has been developed. Based on the proposed model we performed numerical Monte-Carlo simulations, which provide evidence of a fractal expansion of functionalized regions leading to a fractal-seaweeds type of addition. We show that the applications of the model is widespread and includes the description of Birch-like hydrogenation, reductive alkylation and direct radical addition, which allows to evaluate the effect of the size, shape and the quality of a graphene flake on the addition morphology. Graphical abstract: Image 1